2016
DOI: 10.1017/s1751731115002967
|View full text |Cite
|
Sign up to set email alerts
|

Review: In vivo and postmortem effects of feed antioxidants in livestock: a review of the implications on authorization of antioxidant feed additives

Abstract: The pivotal roles of regulatory jurisdictions in the feed additive sector cannot be over-emphasized. In the European Union (EU), antioxidant substances are authorized as feed additives for prolonging the shelf life of feedstuffs based on their effect for preventing lipid peroxidation. However, the efficacy of antioxidants transcends their functional use as technological additives in animal feeds. Promising research results have revealed the in vivo efficacy of dietary antioxidants for combating oxidative stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 122 publications
(124 reference statements)
0
40
0
5
Order By: Relevance
“…Antioxidants (both vitamins and minerals) protect the body from damage by the free radicals and have been used both in humans and animals to prevent or delay cell damage. The supplementation of dairy cows having high SCC with antioxidant vitamins such as Vitamin A, C, and E and β-carotene as well as antioxidant minerals such as selenium, zinc, and copper is very effective in reducing their SCC, normalizing their milk composition, and ensuring an early recovery from mastitis [ 80 , 85 , 112 , 113 ]. Supplementation of inorganic selenium reduced IMI in S. aureus -infected dairy cows as compared to non-supplemented animals [ 114 ].…”
Section: Factors Affecting Milk Sccmentioning
confidence: 99%
“…Antioxidants (both vitamins and minerals) protect the body from damage by the free radicals and have been used both in humans and animals to prevent or delay cell damage. The supplementation of dairy cows having high SCC with antioxidant vitamins such as Vitamin A, C, and E and β-carotene as well as antioxidant minerals such as selenium, zinc, and copper is very effective in reducing their SCC, normalizing their milk composition, and ensuring an early recovery from mastitis [ 80 , 85 , 112 , 113 ]. Supplementation of inorganic selenium reduced IMI in S. aureus -infected dairy cows as compared to non-supplemented animals [ 114 ].…”
Section: Factors Affecting Milk Sccmentioning
confidence: 99%
“…Inclusion of citrus and winery by-products below 200 g/kg DM in ruminant diets has been reported to reduce the occurrence of parakeratosis and acidosis in ruminants [13,63]. However, when elevated levels of citrus pulp were fed, along with low levels of forage, rumen parakeratosis and acidosis occurred in lambs [13].…”
Section: Ruminal Parakeratosis and Acidosismentioning
confidence: 99%
“…Screening plant species has found that bioactive compounds in medicinal plants can also decrease ruminal methane emissions (Bodas et al, 2008(Bodas et al, , 2012Patra, Kamra, & Agarwal, 2006;Patra & Saxena, 2010). Botanicals rich in polyphenols comprise a structurally diverse class of natural products with antioxidative and antiinflammatory effects in farm animals (Augustyniak et al, 2010;Gessner, Ringseis, & Eder, 2017;Salami et al, 2016). In ruminants, using high-concentrate diets that are high in starch and low in fibre can reduce ruminal pH and cellulolytic activity in various metabolic disorders (Alzahal, Kebreab, France, & McBride, 2007;Krause & Otzel, 2006;Owens, Secrist, Hill, & Gill, 1998).…”
Section: Introductionmentioning
confidence: 99%